DAMPAK DARI KERJASAMA TRANS ASEAN GAS PIPELINE (TAGP) TERHADAP PEREKONOMIAN DI INDONESIA - Ricky Yudika Matondang; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
ASEAN member states formulated that there should be a cooperation in the field of gas to maintain energy security. This study is a political economy that explains Indonesia's efforts of gas export activities to ASEAN member countries in 2011-2015 in the Trans ASEAN gas pipeline agreement. The Trans ASEAN gas pipeline agreement has been discussed since the 1970s but was officially codified in 1990. The ASEAN gas pipeline agreement was established because of the awareness of ASEAN member countries on the issue of energy security and the interests of Indonesia as one of the ASEAN member countries to utilize by effectiveness and efficiency to distributenatural resources for the national interest among ASEAN nation.This research uses neo-liberalism as the perspective by James Rosenau. Neoliberalism contains an economic theory that is based on the use of open and free markets with little government intervention to prevent monopolies and other conglomerates from forming. This research use regionalization for level of analysisby Mohtar Mas’oed. This research also use international cooperation as concept by K.J Holsti. The sources in this study were obtained from library research and internet research.Trans ASEAN gas pipeline emerged as one way for ASEAN member countries to meet the national energy needs in the gas field. in this agreement Indonesia as a country that has natural gas reserves sufficient to benefit from efficiency export and increase tax..Keywords : Free Market, Trans ASEAN Gas Pipeline, Energy Security